Mediating Student Teachers through Edmodo in an Extensive Listening Class - Arifiyanto, Satrio; Ali, Fachri (Institut Agama Islam Negeri Kudus, 2019)
This study aims to explore the use of Edmodo as the media in extensive listening class for students teacher. This study was conducted in the class consisted of 46 students who took Extensive Listening course at the university. participants from this study were second semester students of English Education of IAIN Pekalongan. The participants used Edmodo for a full semester where the activities they did are, discussing about the subject material and sending assignments were given by the lecturer. The findings are the participants who used Edmodo actively and they utilized it maximally. The conclusion of this study is using Edmodo in the extensive listening class for student teachers of English Education of IAIN Pekalongan was effective.